STRATEGI PEMASARAN KELOMPOK BIMBINGAN IBADAH HAJI DAN UMROH AL MABRUR LUMAJANG - Fathur Rohman (Institut Agama Islam Syarifuddin Lumajang, 2018)
This study examines the marketing strategies of Hajj Guidance Groups (KBIH/ KelompokBimbinganIbadah HajidanUmroh) Al MabrurLumajang. The method used is qualitative descriptive. The applied Data collection techniques areinterviews, observation and documentation. Data analysis uses descriptive qualitative. The conclusion of this study is the marketing strategy is carried out in four stages: promotion, product provision, affordable prices, and strategic office locations. The marketing supporting factors are the loyalty of consumers, the provision of good services, affordable prices, the existence of alumni ties among Hajj pilgrims, and the number of Al Mabrur KBIH officers who are adequate for Lumajang scope. The factors that hinder marketing are the growth of more competitors, the lack of human resourcesquality, and the absence of KBIH blog and website.